Does Once-Daily Raltegravir Have Any Role in the Antiretroviral Treatment?. Issue 43 (October 2015) - Gutierrez-Valencia, Alicia; Chacón-Mora, Natalia; Ruiz-Valderas, Rosa; Ben-Marzouk-Hidalgo, Omar J.; Torres-Cornejo, Almudena; Viciana, Pompeyo; Lopez-Cortes, Luis F.
Abstract : Abstract: Administering raltegravir once daily would make adherence to antiretroviral treatment easier, especially if the concomitant drugs are also administered once daily. We report our experience on the use of raltegravir, both once- and twice-daily. Retrospective review of HIV-infected patients on treatment with raltegravir 800 mg once or 400 mg twice a day plus 2 analogs. Patients were classified as group A (subjects switched to raltegravir due to adverse events on a previous regimen or drug–drug interactions) and group B (subjects who restarted antiretroviral treatment after a previous drop-out). The primary clinical endpoint was the percentage of subjects with virological suppression after 96 weeks. Treatment's effectiveness (noncomplete/missing equals failure) was also evaluated. Pharmacokinetic study was performed in unselected patients. Plasma raltegravir concentrations were determined by high-performance liquid chromatography coupled with mass spectrometry. A total of 133 patients were included in the study (74 and 59 on raltegravir once- and twice-daily). There were only 4 virological failures in the entire cohort during the follow-up. Thus, the Kaplan–Meier estimation of efficacy by on-treatment analysis was 96.3% (CI95, 92.8–99.8) at week 96, independently of the dosing regimen and of the raltegravir concentrations. Similar exposures to raltegravir based on AUC0– τ, but higher C max and significantly lower C trough were observed when raltegravir was given once daily compared with 400 mg twice daily. In fact, 14 out of 56 C trough concentrations (25%) from patients taking raltegravir once daily were below the IC95 of wild-type HIV-1 clinical isolates while only 2 samples from patients receiving 400 mg twice a day were below this value, although no relationship between C trough and efficacy was found. The main limitations of the study are that the raltegravir dosing regimen was not randomized and more than 50% of the patients were virologically suppressed at baseline. Regimens comprising raltegravir 800 mg once daily plus 2 nucleos(t)ide reverse transcriptase inhibitors can be an efficacious and safe option, particularly in virologically suppressed patients and those with a viral load <100, 000 copies/mL.